Evaluation of Cu, Mn, and Se in Vegetables Using Ultrasonic Extraction and GFAAS Quantification - Federici Padilha, Cilene do Carmo [UNESP]; de Moraes, Paula Martin [UNESP]; Garcia, Luciana de Arruda [UNESP]; Costa Pozzi, Carla Mariane; Lima, Giuseppina Pace Pereira [UNESP]; Serra Valente, Jose Pedro [UNESP]; Alves Jorge, Sonia Maria [UNESP]; Padilha, Pedro de Magalhaes [UNESP] (Springer, 2011)
This paper proposes a method for the determination of copper, manganese, and selenium in vegetables of conventional and organic farming in the state of So Paulo/Brazil using ultrasonic extraction of analytes and subsequent quantification by graphite furnace atomic absorption spectrometry (GFAAS). Using 0.10 mol L(-1) of hydrochloric acid as the extracting solution, the following optimal extraction conditions were established: sample mass of 100 mg, sample grain size of < 60 mu m, sonication time of five cycles of 40 s, and sonication power of 136 W. The analytes were determined by GFAAS, applying drying temperatures of 90 A degrees C to 250 A degrees C, pyrolysis temperature of 1,300 A degrees C, atomization temperature of 2,300 A degrees C, and cleaning temperature of 2,800 A degrees C. Palladium nitrate was co-injected with the samples as a chemical modifier and tungsten as a permanent modifier. The accuracy and precision of the proposed extraction method were evaluated based on a certified standard, RM 8433 Corn Bran (NIST RM 8433). The results obtained by the ultrasonic extraction method were equivalent to those obtained by the method of acid mineralization of samples in a microwave oven. However, the proposed methodology reduces the analytical time considerably, favoring the analytical speed. Moreover, the quantity of residues generated and discharged into the environment is also considerably lower.
Keywords: Micronutrients; Farming system; Conventional; Organic; Ultrasonic extraction; GFAAS